High sensitivity C-Reactive Protein levels and blood pressure status in young adults - Asmak Abdul Samat (Kulliyyah of Medicine, International Islamic University Malaysia, 2018)
C-Reactive Protein (CRP) levels had been recommended in the global risk prediction for cardiovascular diseases (CVD) of asymptomatic individuals. CRP levels vary substantially across diverse population worldwide. Thus, identifying its normal values in our population is necessary for its accurate use as a better predictor of future cardiovascular events and allowing an earlier initiation of preventive measures. This comparative cross sectional study was conducted to compare the hs-CRP concentrations in different categories of blood pressure among young adults (18 and 45 years old) in Kuantan, Pahang, Malaysia. A total of 272 subjects were recruited and categorised into three groups namely normotensive (NT), prehypertensive (PHT) and hypertensive (HPT) according to the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7). Samples were assayed for hs-CRP profile using Siemens Advia 2400 Chemistry System Analyser based on polyethylene glycol (PEG)-enhanced immunoturbidimetric method. The hs-CRP levels of subjects differ between populations in some countries. There was a significant difference between the three groups. The mean (SD) of hs-CRP for NT was 0.77 (1.39) mg/L, PHT and HPT were 1.54 (1.28) mg/L and 2.15 (1.30) mg/L respectively. Hs-CRP was not significantly associated with blood pressure status after adjustment for covariates in this study, however the relationship was confounded by other factors that were age, gender, parent's history of hypertension and BMI status. The risk of developing cardiovascular diseases in 10 years' time was highest in the hypertensive young adults. The predictive value of CRP Risk alone is just as accurate as newly adapted Reynolds Risk Score, in the hypertensive young adults, but not in the prehypertensive young adults. The findings of the study suggest the importance of developing our own rubric on cardiovascular risk assessment based on blood pressure and hs-CRP particularly in young adults.